2022
DOI: 10.1128/iai.00206-22
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae l- Fucose Metabolism Promotes Gastrointestinal Colonization and Modulates Its Virulence Determinants

Abstract: Colonization of the gastrointestinal (GI) tract by Klebsiella pneumoniae is generally considered asymptomatic. However, gut colonization allows K. pneumoniae to either translocate to sterile site within the same host or transmit through the fecal-oral route to another host. K. pneumoniae gut colonization is poorly understood, but knowledge of this first step toward infection and spread is critical for combatting its disease manifestations.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 84 publications
0
27
0
Order By: Relevance
“…Hudson and colleagues demonstrated that K. pneumoniae was also able to utilize mucin-derived fucose to support its growth in the mouse intestine [88]. They found that a K.…”
Section: Introductionmentioning
confidence: 99%
“…Hudson and colleagues demonstrated that K. pneumoniae was also able to utilize mucin-derived fucose to support its growth in the mouse intestine [88]. They found that a K.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the importance of ecological diversity and complexity is observed for both pathogens. We anticipate that the importance of ecological diversity and the principle of nutrient blocking will apply generally, given the widespread evidence that nutrient competition is important for diverse species in the microbiome, including many other pathogens (9,(47)(48)(49)(50)(51)(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the World Health Organization has designated development of novel anti-Klebsiella control strategies an urgent global priority [2]. Many existing antimicrobials target or alter cellular metabolic processes, and recent works have highlighted a role for metabolism in K. pneumoniae virulence [3,4], supporting these processes as prime targets for novel therapeutics. For example, production of the GltA citrate synthase appears to facilitate liver and spleen infections in mouse models [5], while a psicose sugar utilization locus has been associated with lung infection [6].…”
Section: Introductionmentioning
confidence: 99%